Comparative Study of Ultrasound-Guided vs Landmark-Based Pudendal Nerve Block for Labour Analgesia - Farah Naz Memon, Sasui Memon, Fazal Hussain, Zia Ul Islam, Abdul Rehman, Atqa Firdous (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Pudendal nerve block (PNB) is a regional anesthetic procedure frequently performed in the second stage of labor to relieve perineal pain. Traditionally done with anatomical landmarks, ultrasound guidance is an alternative that is considered more accurate. The purpose of this study is to compare the efficacy and safety of ultrasound-guided and landmark-based PNB in parturients during labor. Methods: Participants were randomly assigned to receive USG-PNB or LMR-PNB; a total of 180 parturients was recruited in the study. The onset time of analgesia, duration of analgesia and Visual Analog Scale (VAS) scores for pain relief were the main outcomes measured. Secondary outcomes were the rate of complications and patient satisfaction scores. Results: Onset time of analgesia was significantly shorter and duration longer in the ultrasound-guided group than that in landmark-based. VAS of the ultrasound-guided group was lower than that of the landmarks-guided group, suggesting that pain relief was better. Complications were similar in both groups, and patient satisfaction was greater for the ultrasound-guided group. Conclusion: Ultrasound-guided PNB results in better analgesia and patient satisfaction, without increase of the complication rate when compared with the conventional landmark-based approach. Keywords: Pudendal Nerve Block, Ultrasound Guidance, Landmark-Based Technique, Labor Analgesia, Regional Anesthesia, Obstetric Pain Management